Kewirausahaan Mahasiswa Melalui Perencanaan Bisnis Produk Teh Daun Bidara - Baintjo, Jerikho; Baintjo, Jerikho R S; Wanti, Sri; Yahya, Delviani; Aprilia, Salsabila Irsa; H, Irawan; Benawan, Dea Anggreani Putri; Revaldy, Rafly (Sasambo: Jurnal Abdimas (Journal of Community Service), 2026)
This community service program aims to develop the potential of bidara leaves (Ziziphus mauritiana) as an herbal tea product through student entrepreneurship assistance in Ampana Kota District, Tojo Una-Una Regency. The program employed a SWOT analysis and Business Model Canvas (BMC) approach based on field data. Participants consisted of 25 respondents, including 12 students, 3 local herbal business actors, and 10 community members as potential consumers. Data were collected through observation, in-depth interviews, and focus group discussions, and analyzed using descriptive qualitative methods with source triangulation. The results indicate that bidara leaves are abundantly available throughout the year, possess recognized health benefits, and have strong potential to be developed into value-added herbal tea products. The SWOT analysis revealed key strengths such as stable raw material availability and low production costs, while limitations in production equipment and the absence of product certification emerged as major weaknesses. The BMC design demonstrates a feasible business model emphasizing health-based value propositions and educational marketing strategies. A simple financial simulation shows that the business is economically viable, reaching a break-even point at approximately 100 product packages. Overall, this community service activity highlights the role of students as change agents in integrating innovation, health education, and local resource-based entrepreneurship to support local economic empowerment.